THE EVOLUTION OF ENVIRONMENTAL EDUCATION IN ENVIRONMENTAL LICENSING IN MINAS GERAIS: LESSONS LEARNED AND FUTURE CHALLENGES (Editora Impacto Científico, 2025)
Environmental Education (EE) is a fundamental instrument for promoting socio-environmental justice and strengthening social participation in environmental management processes. In the context of environmental licensing, EE plays a strategic role by contributing to the mitigation of impacts, the expansion of dialogue between social actors, and the legitimization of administrative decisions. This article analyzes the normative and methodological evolution of Environmental Education in environmental licensing in the State of Minas Gerais, with emphasis on COPAM Normative Deliberations No. 110/2007, No. 214/2017, and No. 238/2020. Based on a bibliographic and documentary review, the study discusses the advances and limitations of Environmental Education Programs (EEPs), highlighting the introduction of Participatory Socio-environmental Diagnosis (PSD) as a milestone in the incorporation of dialogical and territorialized practices. Challenges related to effective community participation, the technical and ethical training of environmental educators, the inclusion of traditional and vulnerable populations, and the absence of consistent indicators for evaluating the effectiveness of EEPs are also addressed. Based on theoretical contributions from critical environmental education, hermeneutics, and environmental epistemology, this article argues for the consolidation of environmental education as a structuring axis of environmental licensing, highlighting the need for continuous professional qualification, institutional strengthening, and transversal integration with other public policies. It concludes that, although Minas Gerais has made significant progress, the effectiveness of environmental education in licensing depends on deepening participatory practices, systematic monitoring of actions, and political commitment to the socio-environmental transformation of territories.DOI: https://doi.org/10.56238/edimpacto2025.090-082